The Temporal Pattern of Changes in Serum Biomarker Levels Reveals Complex and Dynamically Changing Pathologies after Exposure to a Single Low-Intensity Blast in Mice - Ahmed, Farid; Plantman, Stefan; Cernak, Ibolja; Agoston, Denes V. (Frontiers in Neurology, 2015)
Time dependent changes of protein biomarkers in the serum can help identifying the pathological processes and assessing the severity and progression of the disease in blast induced traumatic brain injury (bTBI). We obtained blood from naïve mice and mice exposed to a single, low-intensity blast at 2 hour, 1 day, 1 week and 1 month post-injury. We then determined the serum levels of biomarkers related to metabolism (4-HNE, HIF-1α, Ceruloplasmin), vascular functions (VEGF, vWF, AQP1, AQP4, FLK-1), cell adhesion (Integrin 6α, TIMP1, TIMP4, Ncad, Connexin-43), inflammation (MMP-8, MIP-1α, CINC1, Fibrinogen, CCR5, CRP, Galectin-1, MCP-1, p38, OX-44, Osteopontin), axonal (NF-H, Tau), neuronal (NSE, CK-BB) and glial integrity (GFAP, S100β, MBP) and compared the changes among the experimental groups. Our results indicate that in the mouse, exposure to a single, low-intensity blast caused substantial metabolic, vascular and inflammatory responses, altered cell adhesion but only minimal neuronal, axonal and glia injury as indicated by serum proteomics data. Changes in metabolism, vascular functions and inflammation remained elevated at the termination of the experiment while the others were only detectable during the acute post-injury phase. Our findings indicate that exposure to a single; low-intensity blast can induce complex pathological processes with distinct temporal profile. Hence, monitoring serum biomarker levels at various post-injury time points may provide enhanced diagnostics in bTBI.